Physical fitness spurts in pre-adolescent boys and girls: Timing, intensity and sequencing - Pereira, S.; Santos, C.; Tani, G.; Freitas, D.; Garbeloto, F.; Guimarães, E.; Robinson, L. E.; Baxter-Jones, A.; Katzmarzyk, P. T.; Maia, J. (Journal of Sports Sciences, 2022)
We aim to (1) estimate age of attainment of the peak mid-growth spurt in stature (age-at-peak MGS) in pre-adolescent boys and girls; (2) identify the timing, intensity, and sequences of physical fitness (PF) spurts aligned by the age-at-peak MGS; and (3) identify any sex differences in PF spurts aligned by age-at-peak MGS. The sample included 180 Portuguese children (90 girls) aged 6 to 10 years at study entry who were followed annually for 4 years. Height, health-, and performance-related PF were assessed. Age-at-peak MGS and PF spurts were estimated using a non-smooth mathematical procedure. Boys` and girls` age-at-peak MGS occurred at 7.8 ± 0.47 years and 8.0 ± 0.72 years, respectively. PF spurts` timing aligned by age-at-peak MGS were as follows: (1) before age-at-peak MGS: boys - static strength, aerobic capacity, explosive leg strength, and flexibility; girls - speed, agility, aerobic capacity, and upper body strength; (2) coincident with age-at-peak MGS: girls - explosive leg strength and flexibility; (3) after age-at-peak MGS: boys - abdominal strength, upper body strength, agility, and speed; girls - abdominal strength and static strength. Boys and girls attained their MGS at relatively similar ages. However, the timing and sequences of PF spurts, aligned on age-at-MGS, were different between boys and girls.